2009
DOI: 10.3109/17482960903009054
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of ALS is changing: Improved survival

Abstract: In the past two decades new practice parameters for clinical care in ALS were developed and several clinical trials were performed. We sought to review information in these prospective datasets and assess whether natural history of ALS has changed over time. Survival and the rate of functional decline were compared across the placebo arms of efficacy trials conducted from 1999 to 2005 by the Northeast ALS Consortium (NEALS). Similar data from the placebo arms of 12 other published efficacy ALS trials conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 40 publications
5
33
1
Order By: Relevance
“…The use of such data, however, has received mixed reviews amongst the scientific community [152], given the evolving standards of ALS patient care, which have resulted in improved patient survival [153], as well as regional differences in clinical practice.…”
Section: Clinical Trials In Alsmentioning
confidence: 99%
“…The use of such data, however, has received mixed reviews amongst the scientific community [152], given the evolving standards of ALS patient care, which have resulted in improved patient survival [153], as well as regional differences in clinical practice.…”
Section: Clinical Trials In Alsmentioning
confidence: 99%
“…There is a lack of research exploring the relationship between decreasing ALSFRS and %FVC and serum ferritin level elevation. Nemba et al22 showed us that lower BMI and serum insulin-like growth factor 1 (IGF-1) could increase serum ferritin levels in malnourished adolescents with eating disorders 1. Only one report13 picked up the BMI value, we found that the changes of BMI value have relationship with serum ferritin levels.…”
Section: Discussionmentioning
confidence: 74%
“…The elevated heterogeneity and publication bias may be explained by the study design, type of measure of association, geographic area, ferritin assay technique, %Bulbar onset, age at sample, ALSFRS, BMI, %FVC, non-invasive positive-pressure ventilation, oral riluzole, and enteral nutrition 1. Because serum ferritin is an acute-phase reactive protein that can be raised in the presence of acute or chronic inflammation, it changes according to the inflammation levels of ALS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been argued that people with motor neurone disease (MND) are living longer because of improvements in symptomatic care 1. However, this conclusion is based on an analysis of selected patients recruited into the placebo arm of trials.…”
mentioning
confidence: 99%